Estimates of Fractional Integral Operators on Variable Exponent Lebesgue Spaces. (27th June 2016) - Tang, Canqin; Wu, Qing; Xu, Jingshi
Abstract : By some estimates for the variable fractional maximal operator, the authors prove that the fractional integral operator is bounded and satisfies the weak-type inequality on variable exponent Lebesgue spaces.